Fibrinogen Nový Jicín and Praha II: cases of hereditary Aalpha 16 Arg-->Cys and Aalpha 16 Arg-->His dysfibrinogenemia - Kotlín, Roman; Chytilová, Martina; Suttnar, Jirí; Riedel, Tomás; Salaj, Peter; Blatný, Jan; Santrůcek, Jirí; Klener, Pavel; Dyr, Jan E (Thrombosis research, 2007)
INTRODUCTION: Various dysfibrinogenemias have been described worldwide. This paper describes two new cases of dysfibrinogenemia identified in the Czech Republic. MATERIALS AND METHODS: The proposita of fibrinogen Nový Jicín, a 12-year-old girl, presented with hemorrhagic complications, low Clauss fibrinogen level (0.3 g/l) and prolonged both thrombin (70.8 s) and reptilase (>180 s) time. Her mother and sister both presented with normal coagulation tests, normal fibrinogen level and reported no history of bleeding. The carriers of the fibrinogen Praha II were a 31-year-old man and his 11-year-old daughter. They both presented with low fibrinogen Clauss level (0.88 g/l) and prolonged thrombin and reptilase time. To identify the genetic mutation responsible for these dysfibrinogens, genomic DNA extracted from the blood was analyzed. The presence of the mutant chains in the circulation was determined by MALDI-TOF mass spectroscopy. Scanning electron micrographs of the patients' fibrin clots were obtained. RESULTS: The kinetics of fibrinopeptide release and fibrin polymerization were impaired for both fibrinogen Nový Jicín and Praha II. DNA sequencing showed heterogeneous fibrinogen Aalpha R16C mutation in the fibrinogen Nový Jicín case and heterogeneous fibrinogen Aalpha R16H in the fibrinogen Praha II case. The mutant chains were found to be expressed to the circulation by MALDI-TOF mass spectroscopy. Scanning electron micrographs of the patient's fibrin clot were found to be abnormal. CONCLUSIONS: The case of dysfibrinogenemia Aalpha R16C-fibrinogen Nový Jicín and the case of dysfibrinogenemia Aalpha R16H were found by routine coagulation testing and were genetically identified.
Keywords: kinetika; Fibrin; afibrinogenemie; Afibrinogenemia; fibrin; zdraví rodiny; Česká republika; missense mutace; DNA Mutational Analysis; mužské pohlaví; krvácení; vyšetření krevní srážlivosti; Adult; Mutation, Missense; mutační analýza DNA; Czech Republic; dítě; Child; Family Health; Fibrinogens, Abnormal; ženské pohlaví; Humans; Blood Coagulation Tests; Kinetics; Hemorrhage; dospělí; fibrinogeny abnormální; Female; lidé; Male